Formulasi dan Evaluasi Sediaan Lip Scrub dari Madu (Apis dorsata): Formulation and Evaluation of Lip Scrub Preparations from Honey (Apis dorsata) - Awalia Sariningsih; Nur Masyithah Z; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Problems on the skin of the lips are often found such as cracked, which can be solved by routinely using lip scrubs because dead skin cells on the lips need to be excreted. Honey can be used as a moisturizer in pharmaceutical preparations because of its humecant and emollient properties. This study aims to find out if honey can be used as a lip moisturizer and find out how to formulate lip scrub preparations from optimum honey. This research method was conducted experimentally, namely testing the moisture of honey on the lips using a skin analyzer. Then the formulation of lip scrub preparations with variations in honey concentration and physical stability testing which includes organoleptic test, homogeneity, pH, and spread of preparations conducted for 28 days, in addition to being conducted irritant test preparations for 2 days in a row. The results obtained by honey moisture testing on the lips increased water content by 17.6%. The results on the organoleptic test evaluation were brown, oleum rosae smell, and sweet taste. Homogeneity test to determine the homogeneity of lip scrub preparations in the absence of clumping materials that are not dissolved. pH test obtained is a stable semi-solid lip scrub preparation that is at pH 6. Spreadability test obtained diameter of 4 cm. Based on the results of evaluation on lip scrub preparations that have good physical quality and stable in F2 with honey concentration of 6%.